Analisis Kegagalan Laminasi Komposit Epoksi/Serat Karbon Pada Sayap Pesawat Tanpa Awak - Ansor Salim Siregar; Mulyadi Mulyadi; Syaiful Arief (Piston: Journal of Technical Engineering, 2022)
This study aims to analyze the initial failure value using the Tsai – Wu criteria from the wing skin of an unmanned aircraft with the Eppler 214 airfoil model. The study was carried out using computer modeling with Abaqus software. The material used is an epoxy composite which is carbon fiber. The composites used in the wing skins have two different arrangement sequences, namely the fiber layer arrangement sequence 1 [00/900]8s and the layer sequence 2 [00/+450/-450/900]2s. The load given to the wing is a pressure of 0.40077 MPa. The results for the fiber layer sequence 1 [00/900]8s at the maximum stress distribution are 5.067 x 104 MPa and in the fiber layer sequence, 2 [00/+450/-450/900]2s the maximum value is 4.205 x 104 MPa. While the sequences consist of fiber layer 1 and layer 2 sequence layers, the Tsai – Wu failure meets the Tsai – Wu failure criteria because almost all of them fail